Compressive Strain Modulation of Single Iron Sites on Helical Carbon Support Boosts Electrocatalytic Oxygen Reduction - Yang, Jia; Wang, Zhiyuan; Huang, Chun‐Xiang; Zhang, Yida; Zhang, Qinghua; Chen, Cai; Du, Junyi; Zhou, Xiao; Zhang, Ying; Zhou, Huang; Wang, Lingxiao; Zheng, Xusheng; et al. (Angewandte Chemie International Edition, 2021)
Designing and modulating the local structure of metal sites is the key to gain the unique selectivity and high activity of single metal site catalysts. Herein, we report strain engineering of curved single atomic iron‐nitrogen sites to boost electrocatalytic activity. First, a helical carbon structure with abundant high‐curvature surface is realized by carbonization of helical polypyrrole that is templated from self‐assembled chiral surfactants. The high‐curvature surface introduces compressive strain on the supported Fe−N4 sites. Consequently, the curved Fe−N4 sites with 1.5 % compressed Fe−N bonds exhibit downshifted d‐band center than the planar sites. Such a change can weaken the bonding strength between the oxygenated intermediates and metal sites, resulting a much smaller energy barrier for oxygen reduction. Catalytic tests further demonstrate that a kinetic current density of 7.922 mA cm−2 at 0.9 V vs. RHE is obtained in alkaline media for curved Fe−N4 sites, which is 31 times higher than that for planar ones. Our findings shed light on modulating the local three‐dimensional structure of single metal sites and boosting the catalytic activity via strain engineering. Compressive strain engineering of curved single atomic iron‐nitrogen sites could boost the catalytic activity for electrocatalytic oxygen reduction reaction.